Предмет: Алгебра,
автор: ivanpinko
Как решить??? Пожалуйста СРОЧНО!!!!
(z+1)^2=
(3y-4)^2=
(2a-3b)^2=
(-3x+y)^2=
(a-b^3)^2=
Ответы
Автор ответа:
0
(z+1)²=z²+2z+1
(3y-4)²=9y²-24y+16
(2a-3b)²=4a²-12ab+9b²
(-3x+y)²=(y-3x)²=y²-6xy+9x²
(a-b³)²=a²-2ab³+b⁶
(3y-4)²=9y²-24y+16
(2a-3b)²=4a²-12ab+9b²
(-3x+y)²=(y-3x)²=y²-6xy+9x²
(a-b³)²=a²-2ab³+b⁶
Похожие вопросы
Предмет: Биология,
автор: okawaiikoto2859
Предмет: География,
автор: Аноним
Предмет: Английский язык,
автор: 172647
Предмет: Математика,
автор: Goriголовы